Strong summability and properties of Fourier?Laplace series on a sphere - Lasuriya, R. A. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We investigate the behavior of quantities that characterize the strong summability of Fourier - Laplace series. On this basis, we establish some properties of the Fourier - Laplace series of functions of the class L_2(S^m-1).